2009
DOI: 10.1074/jbc.m109.005603
|View full text |Cite
|
Sign up to set email alerts
|

Engulfment of Axon Debris by Microglia Requires p38 MAPK Activity

Abstract: The clearance of debris after injuries to the nervous system is a critical step for restoration of the injured neural network. Microglia are thought to be involved in elimination of degenerating neurons and axons in the central nervous system (CNS), presumably restoring a favorable environment after CNS injuries. However, the mechanism underlying debris clearance remains elusive. Here, we establish an in vitro assay system to estimate phagocytosis of axon debris. We employed a Wallerian degeneration model by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
77
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 29 publications
(35 reference statements)
4
77
0
Order By: Relevance
“…Our data support earlier studies showing that phagocytosis and degradation of apoptotic neurons by microglia was accomplished within 2 h (Parnaik et al, 2000). Rapid removal of degenerated myelin sheaths and axonal debris is required for axon regeneration and remyelination (Tanaka et al, 2009). In addition, persistence of tissue debris is more likely to lead to autoimmunity.…”
Section: Discussionsupporting
confidence: 81%
“…Our data support earlier studies showing that phagocytosis and degradation of apoptotic neurons by microglia was accomplished within 2 h (Parnaik et al, 2000). Rapid removal of degenerated myelin sheaths and axonal debris is required for axon regeneration and remyelination (Tanaka et al, 2009). In addition, persistence of tissue debris is more likely to lead to autoimmunity.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, OPN appears not to be involved in the process of phagocytosis of the axon and myelin debris. In support of this, Tanaka et al (2009) suggested that ligands and receptors for phagocytosis of the dying neurons might be different from those for phagocytosis of the axon and myelin debris.…”
Section: Discussionmentioning
confidence: 92%
“…BINCs may be involved in the removal of degenerated tissue debris by phagocytosis, since they bear phagosomes that internalize degenerated materials, as has been shown by immunoelectronmicroscopic observations . Removal of cell or tissue debris is shown to facilitate the regeneration of neural processes (Tanaka et al, 2009). BINCs or highly proliferative microglia-like cells can differentiate into new neurons and glial cells, as described in several reports (Butovsky et al, 2007;Niidome et al, 2008;Yokoyama et al, 2006), although it is difficult to evaluate the significance of this for regeneration of damaged brain tissue.…”
Section: Discussionmentioning
confidence: 99%